A 25-year odyssey through luxury tourism research - Sudarsono, Aji (Academica turistica, 2025)
This study conducts a bibliometric and systematic literature review (SLR) of luxury tourism research, analysing 72 Scopus-indexed articles from 2000 to 2025. The findings reveal a growing interest in luxury tourism, with publication peaks in 2024 (14 articles) and notable growth between 2022 and 2023. Italy leads in research output (8 articles), followed by the UK, New Zealand, and China (7 each), while developing nations like Indonesia remain underrepresented. Thematic analysis identifies key clusters, including socio-economic impacts, luxury consumer behaviour, and sustainability in hospitality. Research predominantly employs qualitative methodology (38 studies) as the primary data collection tool. Emerging trends emphasize digitalization, sustainability, and experiential luxury tourism, with increasing use of AI, machine learning, and social media analytics. The study highlights the multi disciplinary nature of luxury tourism, intersecting with business, social sciences, and environmental studies. Mixed-method approaches are gaining traction, blending qualitative depth with quantitative generalizability. Key challenges include balancing luxury tourism’s economic benefits with sustainability and addressing in frastructural gaps in emerging destinations. The VOSviewer analysis underscores global research collaborations, with Europe and Asia as dominant contributors. Practical implications suggest that stakeholders should prioritize sustainable practices, digital marketing, and personalized experiences to cater to luxury tourists. Future research should explore developing markets, cultural influences, and policy impacts to enrich the global understanding of luxury tourism dynamics.
Keywords: bibliometric analysis; bibliometrična analiza; consumer behaviour; digitalizacija; digitalization; luksuzni turizem; luxury tourism; PRISMA; sistematični pregled literature; systematic literature review; vedenje potrošnikov